2004
DOI: 10.1158/1078-0432.ccr-040006
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression as a Predictive Marker of Outcome in Stage IIB-IIIA-IIIB Non-Small Cell Lung Cancer After Induction Gemcitabine-Based Chemotherapy Followed By Resectional Surgery

Abstract: Patients with RRM1 levels in the bottom quartile benefited significantly from gemcitabine/cisplatin neoadjuvant chemotherapy, leading us to conclude that RRM1 mRNA levels should be additionally validated to proceed with tailored chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
2
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 20 publications
3
77
2
6
Order By: Relevance
“…Furthermore, two clinical studies have demonstrated that the assessment of hENT1 and RRM1 is useful in order to predict the response to gemcitabine in pancreas and lung cancer, respectively (38,53). Our previous study has also indicated the importance of RRM1 as a possible chemoresistance marker for gemcitabine in BTC (48).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, two clinical studies have demonstrated that the assessment of hENT1 and RRM1 is useful in order to predict the response to gemcitabine in pancreas and lung cancer, respectively (38,53). Our previous study has also indicated the importance of RRM1 as a possible chemoresistance marker for gemcitabine in BTC (48).…”
Section: Discussionmentioning
confidence: 98%
“…RRM1 has been shown to function with the p53-regulated RRM2 homologue p53R2, which is important in DNA repair secondary to genotoxic stress [11]. In in vitro studies, increased RRM1 expression and activity has been shown to be a marker for gemcitabine resistance [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the multifactorial nature of platinum resistance and therefore the difficulty in using DNA repair proteins as markers of platinum resistance in the clinic. Some trials have found an association between ERCC1 and response to cisplatin combination therapy [28][29][30], but many more have found no association [31][32][33][34][35]. High ERCC1 may correlate with platinum resistance, but low or absent ERCC1 may not always indicate sensitivity as the H69CIS200 and H69OX400 when actively dividing show no change in ERCC1 despite being platinum resistant.…”
Section: No Change In Dna Repair Capacity Associated With Platinum Rementioning
confidence: 99%